Albert Schweitzer se etiese gesigseinder: Eerbied vir en dankbaarheid teenoor die lewe - Botha, Pieter JJ (Stellenbosch Theological Journal, 2016)
Albert Schweitzer’s ethical horizon: reverence and gratitude for life In the search for relevant theology, especially in the context of the ethical and moral challenges facing contemporary South Africa, the theology/philosophy of religion of Albert Schweitzer can play an important role. Aspects of Schweitzer’s deliberations are briefly discussed under three topics: ethical mysticism, the centrality of life and the responsibility associated with living. The famous statement, “reverence for life” as summary for Schweitzer’s thinking is embedded in profound and comprehensive reflection, and properly understood can provide meaningful support to contemporary theologies struggling with the faith-action divide.